PENINGKATAN HASIL BELAJAR MATA KULIAH DISAIN BUSANA II MELALUI PEMBELAJARAN KONTEKSTUAL - Sawitri, Sicilia (Lembaran Ilmu Kependidikan, 2007)
Some efforts to increase student performance in Fashion Design II have beendone in many ways. One of those ways is applied one of instructional approach, forexample: Contextual Teaching and Learning. This approach focuses on holisticlearning and has some aims, such as: to help student to understand teaching materialby connecting with everyday life context. By this approach student will haveknowledge and skill which can applied flexibility from one case to another caseswhich related to fashion design. The main components in contextual teaching-learningare: constructivism, questioning, inquiry, learning community, modeling and authenticassessment. The implications of contextual teaching-learning on Fashion Design II areto give opportunity to the students constructing their knowledge and skill byquestioning, by inquiry, by doing some experiments in fashion design.Key words: pembalajaran kontekstual, desain busana II, hasil belajar